PENGARUH KOSENTRASI PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) TERHADAP JUMLAH ANAKAN DAN PANJANG DAUN RUMPUT GAJAH KERDIL ( Pennisetum purpureum CV. Mtt ) - Irawan Yandri; Supranoto Supranoto; Susilo Rahardjo; Wida Nurnaningsih (MEDIA PETERNAKAN, 2024)
Providing PGPR to the soil around the plant can influence the growth and fresh production of Pygmy Elephant grass. This research aims to determine the effect of PGPR Mutiara Alam Tani on the number of tillers and leaf length. The research was carried out experimentally using (RAL) with 5 treatments and 4 repetitions consisting of treatment PO = Dwarf Elephant Grass (control) without the addition of PGPR; Treatment P1 = Dwarf Elephant Grass + PGPR 2.5 ml/liter water/m2; Treatment P2 = Dwarf Elephant Grass + PGPR 5 ml/liter of water/m2; Treatment P3 = Dwarf Elephant Grass + PGPR 7.5 ml/liter of water/m2; Treatment P4 = Dwarf Elephant Grass + PGPR 10 ml/liter water/m2). The parameters measured are the number of tillers and leaf length. The results showed that the highest number of tillers was shown in the P4 treatment where 10 ml of PGPR was added in 1 liter of water producing an average number of 5.50 tillers, while the lowest number of tillers was in the P0 treatment which did not add PGPR which produced an average number of tillers. 4.25 tillers. The longest leaves were found in treatment P4 where 10 ml PGPR was added in 1 liter of water with an average length of 75.75 cm, while the shortest leaf length was found in treatment P0 where no PGPR was added resulting in an average weight of 64.75 cm. The results of the analysis showed that the administration of PGPR Mutiara Alam Tani had no significant effect (P>0.05) on the number of tillers and leaf length of Dwarf Gajah Grass. Based on the results of the analysis of variance, it showed that P0, P1, P2, P3 and P4 had the number of tillers and leaf length which is relatively the same. So it can be concluded that the provision of PGPR Mutiara Alam Tani has not been able to influence the number of tillers and the yield of Dwarf Gajah Grass leaf length.